Security＆ safety protection solution of ICS - Qi LIANG (Dianxin kexue)
According to the oil field ICS architecture,combined with the current network security technology,all kinds of risks faced by the industrial control system were analyzed,and a complete set of industrial security ＆amp; safety protection scheme standard for the energy industry was put forward.